(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2021)
Background: Conventional nasal septal surgery depending on head light improves the nasal airway but leaves some complications, but with recent advancement in endoscopic approach limits the complication and improves the outcome. This is due to better visualization, improved illumination, avoiding unnecessary manipulation, limited exposure and scope for second surgery if required. Aim and objective: To assess the functional outcome of endoscopic septoplasty over conventional septoplasty. Material and method: This study was carried out in the department of Otolaryngology – Head & Neck Surgery of Bangladesh Medical College Hospital and Popular Medical College Specialized Hospital over a period of 5 years (2014- 2019). Ethical clearance was obtained from Hospital authority. All consecutive patients with symptomatic deviated nasal septum who were refractory to medical treatment were included in the study. Patients were equally divided into two groups of conventional and endoscopic septoplasty. Patients & their attendants, or legal guardians (in patients of less than 18 years) were thoroughly briefed about the each operative procedure. Patients with acute rhinitis or allergic rhinitis or vasomotor rhinitis or upper respiratory tract infection, external deformity, patients unfit for surgeries and patients not giving consent were excluded from the study. After surgery all patients were followed up monthly, 3 monthly and 6 monthly for 01 year. At each follow up visit, subjective and objective assessments were done. Objective assessment was done by Gertner-Podoshin plate and diagnostic nasal endoscopy. Results: In this study, nasal obstruction was relieved in 91% of conventional and 95% in endoscopic septoplasty group. Headache was improved in 75.68% and 86.5% patients and snoring was improved in 79.5% & 88.6% of patients of respectively. Intraoperative complications such as hemorrhage (21.67% vs 3.33%) and mucosal tear (28.33% vs 5%) are significantly higher in conventional septoplasty group than the endoscopy group. Conclusion: The use of endoscope in septal surgery improves visualization, illumination, and thus reduces complication with improved functional outcome. It can be performed in other diseases of nose and para nasal sinus diseases in the perspective of functional endoscopic sinus surgery. J Bangladesh Coll Phys Surg 2021; 39(3): 178-184